Insan Global Reach: Kolej Permata Insan’s Strategic Internationalisation Plan - Zulkarnin Zakaria; Tg Ainul Farha Tg Abdul Rahman; Liyana Amalina Adnan; Myra Aidrin Mohd Ali (SCIENTIFIC RESEARCH PUBLISHING, 2024)
Creative Education Volume 14, Issue 11 Page (2338-2444)